Determination of Calcium in Foods by the Atomic Absorption Spectrophotometric and Titrimetric Methods - Siong, Tee.E; Khoor, Swan Choo; Shahid, Siti Mizura (1989)
This report presents results of a comparative study of the determination of calcium in a wide variety of foods using the atomic absorption spectrophotometric (AAS) and potassium permanganate titration methods. Ash solution for each food sample (determined in duplicate) was prepared and an aliquot subjected to AAS analysis, while another aliquot was determined by the titrimetric method. A total of 132foods, belonging to 8 food groups were studied. Mean values for duplicate analysis of each food determined by the two methods were tabulated according to food groups. Results obtained by the AAS and titrimetric methods showed good general agreement, and a high correlation coefficient (r = 0.998) was obtained. This was confirmed by paired t-test which showed that for 6 of the food groups studied, there was no statistically significant difference (p < 0.05) in calcium concentrations determined by the two methods. For the remaining 2 groups, legumes and vegetables, a significant difference in results was obtained. However, in both cases, the t-statistic calculated was small. Both methods were found to give mean percent recovery values which were not significantly different and close to 100. There was also no significant difference in variances given by the two methods. Results of the study therefore have shown that either method can be used satisfactorily for the analysis of this nutrient. The choice of method, however, also depends on various other factors, including availability of required instrument and expertise.